The B2B social media book : become a marketing superstar by generating leads with blogging, Linkedln, Twitter, Facebook, e-mail, and more - Bodnar, Kipp, 1982-; Cohen, Jeffrey L., 1965- (Hoboken, N.J. : Wiley, 2012)
Advance your B2B marketing plans with proven social media strategies Learn social media's specific application to B2B companies and how it can be leveraged to drive leads and revenue. B2B marketers are undervalued and under appreciated in many companies.
Includes bibliographical references (p. 205-208) and index.
Keywords: Internet marketing; Social media -- Economic aspects; Online social networks -- Economic aspects; Social media -- B2B.